Karakteristik Struktur Bawah Permukaan Sesar Palu-Koro Berdasarkan Integrasi Analisis Anomali Gravitasi dan Fast Sigmoid Edge Detection (FSED) - Devid Iman Santoso; Supriyadi Supriyadi; Muhamad Syirojudin; Khalil Ibrahim (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to characterize the subsurface structure of the Palu-Koro Fault through the integration of gravity anomaly analysis and the Fast Sigmoid Edge Detection (FSED) method. The study employed the gravity method using Complete Bouguer Anomaly (CBA) data derived from GGMplus/SRTM2Gravity2018. The data were analyzed through regional-residual anomaly separation and potential field derivative analyses, including Derivative-X, Derivative-Y, Derivative-Z, Horizontal Gradient Magnitude (HGM), Tilt Angle (TA), Tilt Angle Horizontal Gradient (TAHG), and FSED. The results indicate that the main trace of the Palu-Koro Fault is characterized by high gravity gradients, consistent sign changes in the Tilt Angle, and strong, continuous FSED responses. Rose diagram analysis of lineaments reveals dominant north–south to northwest–southeast orientations that are consistent with the regional fault trend. In conclusion, the integration of multiple gravity anomaly attributes effectively delineates the geometry and structural segmentation of the Palu-Koro Fault, demonstrating its potential as a reliable approach for active fault mapping and providing an important scientific basis for seismic hazard assessment in Central Sulawesi.  Keywords: FSED, GGMplus/SRTM2Gravity2018, Gravity Anomaly, Palu-Koro Fault, Subsurface Structure, Tilt Angle